The Imaginary of China: Sameness and otherness from the perspective of Macau - Costa, C. M. (Colonial legacies and contemporary studies of China and Chineseness: Unlearning binaries, strategizing self, 2020)
Macao embodies two strong cultural and social legacies, the Chinese and the Portuguese. In this territory, the furthermost tips of the Eurasian landmass meet as well as the two most spoken languages of the northern and southern hemispheres. For over 500 years it has been one of the most internationalised territories in the world. Macau is the product of a negotiated settlement, but it also became a place for other traders from the commercial network of the Portuguese in the Far East and afterwards the place where Europeans and North Americans stayed until they were authorised to go to the inland. Well before the creation of Hong Kong colony, Macau was a place of coexistence, exchange convergence, and newness. Literature and periodical press had an essential role in the circulation of ideas about China and the colony itself. The publication of fiction, opinion, news and religious texts in different languages, mainly in Chinese, Portuguese and English, are sources helping to characterise the international environment of Macau. This evidence also brings to light the specificity of Macau in the region and within the context of Portuguese colonialism. The territory had, from the beginning, particular characteristics in its political administration, which resulted in a particular type of solution. Sovereignty tended to be shared, instead of deploying a straightforward, line, one-directional, top-down colonial template. Instances of this fluid governance model were apparent in the sea and shore governance scheme or in the case of the Chinese population entering and leaving Macau, for work or other economic activities. This political coexistence gave place to a social and cultural interacting coexistence, and at the same time, it occasioned a “communicating hybridity” characterised by syncretism and generative interaction, which the Macanese are the most representative example. From the trends of coexistence and syncretism, a creative intellectual atmosphere developed that allowed for the encounter and crossing of diverse perspectives not only on China but on the territory. This work based on the intellectual perspective aims to analyse the convergence and disparity of imaginaries of China and the Chinese, departing from their textual representation, since the end of the 19th century until the ’30s of the 20th century. Sameness and otherness coexist and sometimes mingled, embodying the diversity existing in the territory, which became one of the significant elements of Macau’s character.